POLITICAL AND LEGAL PHILOSOPHICAL FRAMEWORK FOR NOTARY PUBLIC POSITIONS AS AN ALTERNATIVE FOR DISPUTE RESOLUTION IN INTERNAL POLITICAL PARTY DISPUTES - Muttaqin, Imam Choirul (NOMOI Law Review, 2024)
Political and legal arrangements for mechanisms for resolving internal political parties' disputes have not been effective even though the arrangements have been in place and have changed several times since the beginning of reform until now . In recent years, it can be said that the ideal role and function of political parties is not as ideal. Prolonged internal conflict in several political parties , as public organizational entities Conflict or dispute resolution is an inherent part of political parties. This means that the basic principle of dispute resolution is to minimize state mechanisms (administration and justice ). In this research the author uses a normative juridical approach which departs from the reality of resolving internal political party conflicts so far, thus producing ideas by trying to offer alternative dispute resolution by viewing political parties as legal entities which in legal traffic always have a Notary who always accompanies the deed product. . Philosophically, notaries in exercising their authority are in the realm of evidence, thus, notaries with their deeds become the first filter or front guard in the selection process for 'validity' or validation of the truth of the highest forum as outlined in the deed or its copy as a 'prerequisite' for truth.